Morfologia, germinação e produção de mudas de leguminosas arbóreas ocorrentes na Mata do Pau-Ferro, Areia - Paraíba - Braz, Maria do Socorro Souto (2007)
Mata of Pau-Ferro constitutes an of the most important reservations of vegetation of altitude swamps in the state of Paraíba, Northeast Brazilian, with arboreal representatives of economical importance and thoroughly distributed in other formations of swamps. The objective this work as to characterize morphologically fruits and seeds, besides the phases of germination, seedling, and seedling production of eight forest species found in Mata of Pau-Ferro, municipal district of Areia, state of Paraíba, Northeast Brazilian. Inga ingoides (Rich.) Willd., Acacia polyphylla DC., and Enterolobium contortisiliquum (Vell.) Morong, (Leguminosae-Mimosoideae); Caesalpinia ferrea var. parvifolia Benth., Hymenaea courbaril L., and Pterogyne nitens Tul., (Leguminosae- Caesalpinioideae); Bowdichia virgilioides Kunth. and Erytrina veluntina Willd., (Leguminosae-Papilionoideae) were studed. Were observed, legume “nucóide”, “samaróide” and “bacóide”, types in alls species except, in Erytrina.velutine with occurrence folliculo type. Many species showed epigous germination with fanerocotiledonar seedling and semi- hipogeal germination with criptocotiledonar seedling in Inga ingoides.